(untitled) (Research, Society and Development, 2020)
This article aims to analyze environmental policies based on an assessment of the challenges and perspectives of the municipality of Ijuí / RS, thus contributing to the discussions on the admission of evaluation to the environmental policy cycle at the municipal level, debating challenges and expectations that arise. In this sense, a historical apparatus of the evolution of the evaluation is carried out, providing discussions of concepts, classification and ways of evaluation and finally the evaluation of environmental policies, based on the assumptions that instruments developed for the analysis of social policies allow to be adapted to measure environmental policies, and tools in the environmental field can also contribute to the evolution of the field of study. The research is classified in relation to the objectives as descriptive, in relation to the procedures as case study, had a qualitative approach, and the data collection was done through document analysis and informal interview using the model proposed by Mickwitz (2003). The conclusions show that the demand at the Municipal Environment Department is growing every day due to greater inspection and the need to comply with environmental legislation. At first, perhaps public environmental policies are seen only as obligations, but it is important to evaluate criteria related to the participation of the community and the Councils in decision-making and actions related to public policies in the environment sector.